A Comparative Study of Secondary School Principals’ Instructional Leadership Roles: Turkey – England Example - Sakin, Meliha (2016)
The purpose of this dissertation was to provide a comprehensive understanding of secondary school principals’ instructional leadership roles in Turkey by comparing the behaviours and actions of principals in England with those of their counterparts in Turkey. It investigates the extent to which they are involved in instructional leadership activities, what they understand of this notion, how they enact instructional leadership, what challenges they face as instructional leaders, and which factors explain the differences between Turkish and English educational contexts. The research was conducted using qualitative methods. Semi-structured interview were used to collect the data which was analyzed using a content analysis approach. The Turkish sample of the research studied 4 secondary school principals in the Toroslar district of Mersin selected by a convenience sampling method, whereas 3 principls of secondary schools in the Ashfield district of Nottinghamshire were chosen using a snowball method. The result of the research shows that instructional leadership is understood and enacted in different ways in centralized (Turkey) and partially decentralized (English) educational contexts. Results indicated that instructional leadership behaviours were constrained by many internal and external variables in Turkey many of which are outside of the principal’s control. These included a lack of infrastructure steming from financial incapabilities, lack of internal accountability, lack of personel, and double shift schooling arising from bureaucracy. In contrast, the decentralisation of educational practices within the English context in schools ensures the emergence of shared and distributed leadership, while various factors have directly and indirectly affected the instructional leadership for school improvement. Consequently, this study, with its comparative perspective, adds new insights into the contextually bound nature of instructional leadership which is inevitably affected by the degree and quality of either centralisation or decentralisation.